2021
DOI: 10.1021/acscatal.1c02267
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Total Biosynthesis of Plant Terpene Natural Products Using an Orthogonal Cofactor Regeneration System

Abstract: Here we report the one-pot, cell-free enzymatic synthesis of the plant monoterpene nepetalactol starting from the readily available geraniol. A pair of orthogonal cofactor regeneration systems permitted NAD+-dependent geraniol oxidation followed by NADPH-dependent reductive cyclization without isolation of intermediates. The orthogonal cofactor regeneration system maintained a high ratio of NAD+ to NADH and a low ratio of NADP+ to NADPH. The overall reaction contains four biosynthetic enzymes, including a solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…We therefore hypothesized that addition of the MLPL from Nepeta mussinii (a.k.a Nepeta racemosa ), which is specific for the stereochemistry found in strictosidine, would enhance flux through the pathway in N. benthamiana . Recent efforts at reconstitution in yeast 31 and cell-free 42 systems have also indicated that this enzyme substantially enhances yield.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore hypothesized that addition of the MLPL from Nepeta mussinii (a.k.a Nepeta racemosa ), which is specific for the stereochemistry found in strictosidine, would enhance flux through the pathway in N. benthamiana . Recent efforts at reconstitution in yeast 31 and cell-free 42 systems have also indicated that this enzyme substantially enhances yield.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore hypothesized that addition of the MLPL from Nepeta mussinii (a.k.a Nepeta racemosa ), which is specific for the stereochemistry found in strictosidine, would enhance flux through the pathway in N. benthamiana. Recent efforts at reconstitution in yeast 31 and cell-free 66 systems have also indicated that this enzyme substantially enhances yield.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesise that MLPL might similarly enhance secoiridoid metabolic engineering in microorganisms such as yeast (Brown et al 2015). Indeed, a cell-free in vitro one-pot enzyme cascade included MLPL with nine other pathway enzymes, accessory proteins, and cofactor regeneration enzymes to produce ~1 g/L nepetalactone (Bat-Erdene et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The cell-free biocatalytic synthesis of the corrin metabolite hydrogenobyrinic acid from aminolevulinic acid, which uses 12 overexpressed enzymes for catalyzing 17 reaction steps in one pot, has been achieved with an overall yield of 20% (Roessner et al, 1994;1995). A cell-free system containing nine enzymes, including auxiliary enzymes and cofactor regenerating enzymes, enabled the one-pot synthesis of nepetalactol or nepetalactone starting from geraniol at a much higher product concentration of about 1 g L −1 than the highest titer described for microbial systems (Bat-Erdene et al, 2021). The use of cell-free systems is highly attractive due to its modularity and continues to attract much interest in cell-free metabolic engineering (Dudley et al, 2015;Swartz, 2018) and synthetic biochemistry (Bowie et al, 2020).…”
Section: Cell-free Versus Whole-cell Biocatalytic Systemsmentioning
confidence: 99%